MENINGKATKAN PERILAKU CUCI TANGAN MELALUI METODE BERNYANYI - Yuni K. Prajawati; Mira Triharini; Candra P. Asmoro (Pediomaternal Nursing Journal, 2014)
Introduction: Lack of information in hand washing caused by less attention to hand washing’s behavior in children. Hence, health education was needed and very important in maintaining a healthy because the average transmission of the disease can be spread by hand. This study was aimed to analyze the effect of health education using singing method to improve preschool’s hand washing knowledgeand action. Methods: The population in pre-experimental study (one group pre-post test design) were students B class at Aisyiyah 48, Kindergarten, Surabaya in Juni 2014. The 35 respondents who met inclusion-criteria were taken with total random sampling technique. The data were collected by using structured interview and observation. The data were analyzed by wilcoxon signed rank test with signification value was α≤0,05. The result showed an increase of preschool’s knowledge and action. Preschool’s knowledge and action have scores less than 0,005. Results:The Wilcoxon Sign Ranked Test score revealed p=0.000 for knowledge and p=0.000 for action. It means there was asignificant difference in knowledge and action of hand washing of preschool children at Aisyiyah 48 Kindergarten, Surabaya. The result showed that health education using singing method given significant effects toward the change of hand washing knowledge and action.Conclussion: It is recommended for nurses to apply the singing method to providing health education especially in preschool’s hand washing